Peran dan Fungsi Manajer Keperawatan di Puskesmas - Ricky Riyanto Iksan; Roza Indra Yeni; Rima Berlian Putri; Wiwie Herdalisa; Salamah Thomasita Batubara (Journal of Telenursing (JOTING), 2023)
This study aims to determine the role and function of the nursing manager at the puskesmas. The method used is a case study with a situational analysis of data obtained through interviews and document studies. The stages start from assessment, problem identification, problem analysis, problem priority setting and making a plan of action. The intervention starts with drafting guidelines and self-assessment, hiring experts, outreach and evaluation. The study results indicate that the nursing manager's role and function can be improved by developing guidelines and self-assessment referring to the literature, which includes three main managerial roles and five management functions with an average self-assessment value of 95%, which can be implemented. In conclusion, the role and function of the head of nursing are vital in supporting nursing governance and improving nurse performance. Keywords: Management Function, Nursing, Manager, Role